DAMPAK PEMBENAHAN ULTISOL BANYUMAS DENGAN ASAM ORGANIK TERHADAP PERTUMBUHAN DAN HASIL PADI GOGO ( IMPACT OF BANYUMAS ULTISOL AMELIORATION WITH ORGANIC ACID ON GROWTH AND PRODUCTION OF UPLAND RICE ) - , Haryanto; Widarawati, R. (Pembangunan Pedesaan, 2010)
A study at the Faculty of Agriculture experiment station Navan General Soedirman University aims to 1) determine the impact of organic acids on growth and production of upland rice, 2) find the best varieties of varieties of response which is attempted, and 3) understand the interaction between the organic acid concentration with rice varieties gogo a try, which was conducted in July through October 2009. The experiment was arranged in a randomized block design (RAK) factorial pattern. Three different varieties of upland rice varieties Bagendit Situ, Ciherang, and Cirata as the first factor. The second factor in the form of organic acid concentrations: 0, 50, 100, and 150 g/L distilled water. The parameters observed were plant height, root length, total number of tillers per hill, dry weight of canopy, root dry weight, number of panicles per hill, number of filled grain per panicle, total grain weight, grain and 1000 grain weight. The results showed that the citric acid concentration significantly affected all variable except the number of filled grain per panicle and 1000 grain weight of grain; highest variable achieved at concentrations of 50 g/L distilled water. The use of varieties significant effect on all observed variables except root length. Variety Situ Bagendit provide the best response compared with Ciherang and Cirata; is the interaction between concentration of citric acid and varieties that will try only to give real effect on root dry weight and number of panicle per hill.